Dual physically and chemically crosslinked regenerated cellulose – Gelatin composite hydrogels towards art restoration. (15th April 2020) - De France, Kevin J.; D'Emilio, Electra; Cranston, Emily D.; Geiger, Thomas; Nyström, Gustav
Graphical abstract: Highlights: Dual physically and chemically crosslinked regenerated cellulose – cinnamoyl modified-gelatin composite hydrogels were prepared. Dual crosslinked hydrogels showed enhanced compressive modulus and increased water retention versus purely physically crosslinked hydrogels. Dual crosslinked hydrogels elicited less swelling and hydrophilic paint additive extraction when applied to acrylic-based paint surfaces. This approach has potential for use in applications spanning the conservation of cultural heritage artefacts. Abstract: Art restoration poses many challenges for scientists and conservators, as any restorative action can lead to lasting modification or damage to the original artefact. Recent interest in gel encapsulation has grown due to the ability to control the cleaning action; yet the restoration of modern paints such as acrylic-based systems still presents issues due to their extremely high sensitivity to most solvents. Herein, the preparation of dual physically and chemically crosslinked hydrogels based on regenerated cellulose and cinnamoyl-modified gelatin is demonstrated. These dual crosslinked hydrogels show increased mechanical strength and enhanced water retention compared to pure physically crosslinked hydrogels. When applied to acrylic-based paint surfaces, the dual crosslinked hydrogels extract a smaller amount of hydrophilic additives (albeit still leading to swelling within the paint film) versus physically crosslinked gels. It is anticipated that this dual crosslinking approach can be broadly applied to prepare gels for conservation of cultural heritage artefacts.